Penerapan Good Environmental Governance pada Praktik Perdagangan Karbon di Proyek Katingan Mentaya: The Implementation of Good Environmental Governance in Carbon Trading Practices at Katingan Mentaya Project - Sukadi, Bimo Dwi Nur Romadhon; Pinatih, Dewa Ayu Agung Intan; Sari, Ni Putu Mirna (Pusjar SKPP Lembaga Administrasi Negara, 2020)
The implementation of good governance by continuing to prioritize respect for the environment (good environmental governance) is very suitable to be applied during the environmental problems that occur recently. The implementation of good environmental governance in carbon trading practices in the Katingan Mentaya Project ishe collaboration between the government, private sector, and community, which becomes the main focus of this research. The division of power, duties and authority among the stakeholders is analyzed with 3 principles of good environmental governance. This study revealed an academic study related to â€œthe increasing degree of power-sharing between state and market actorsâ€, where the division of roles between the government and market actors in stage of expanding towards an ideal position. The government (KLHK) is still developing its role as a regulator, while market actor (PT. RMU) is still exploring its potential efforts based on the midst of environmental and community empowerment at Katingan Mentaya Projectâ€™s area. The existed of a statue or legal product that contains carbon trading mechanisms based on the principle of non-overlapping good environmental governance is very necessary for alleviating problems and obstacles that arise. Keywords: Good Environmental Governance, Carbon Trading, Katingan Mentaya Project Abstrak Penyelenggaraan pemerintahan yang baik dengan tetap mengedepankan penghormatan terhadap lingkungan (good environmental governance) sangat sesuai untuk diterapkan di tengah permasalahan lingkungan yang kerap terjadi belakangan ini. Penerapan good environmental governance dalam praktik perdagangan karbon di Proyek Katingan Mentaya, yang merupakan kolaborasi antara pemerintah, swasta, dan masyarakat menjadi fokus utama dalam penelitian ini. Pembagian kekuasaan, tugas, dan wewenang di antara para pelaksana yang terlibat dianalisis dengan tiga prinsip good environmental governance. Penelitian ini mengungkapkan kajian akademik terkait â€œthe increasing degree of power sharing between state and market actorsâ€, yaitu pembagian peran antara pemerintah dan pelaku pasar dalam tahap berkembang (expanding) menuju posisi ideal. Pemerintah (KLHK) masih terus berkembang dalam perannya sebagai regulator dalam menciptakan kebijakan, sedangkan pihak swasta (PT. RMU) masih dalam tahap menggali potensi dengan tetap memperhatikan usaha yang berbasis lingkungan dan upaya pemberdayaan masyarakat di area Proyek Katingan Mentaya. Kehadiran suatu statue atau produk hukum yang memuat tentang mekanisme perdagangan karbon berdasarkan prinsip good environmental governance yang tidak tumpang tindih tentu saja sangat diperlukan, dalam mengentaskan permasalahan dan penghambat yang timbul. Kata Kunci: Good Environmental Governance, Perdagangan Karbon, Proyek Katingan Mentaya